EDUCAÇÃO E DIVISÃO SEXUAL DO TRABALHO: CONFLITOS E DILEMAS ENFRENTADOS POR PROFISSIONAIS HOMENS NOS CENTROS DE EDUCAÇÃO INFANTIL DE GOIÂNIA - Irene Silva de Abreu (2022)
This research deals with gender relations in the field of education, in a context in which there is an increase in the number of male professionals in the environment of Child Education Centers (CEIs) and Municipal Centers for Child Education (CMEIs) of Goiânia, accompanied by some manifestations of displeasure in the school community. This object of study is thus relevant to current discussions and research. The objective is to understand aspects of the sexual division of labor concerning the education and care of children, in order to analyze the conflicts and dilemmas faced by male professionals in the Child Education Centers in Goiânia. Thus, initially a bibliographic survey and literature review was carried out about the historical aspect of the gender issue concerning the professions of child care and education. Next, the field research was carried out, of a quantitative-qualitative nature, in three units of early childhood education of the Municipal Department of Education (SME) of Goiânia, whose instruments used were questionnaires and interviews guided by a semi-structured script. A total of 17 professionals from the researched Child Education Centers participated in the research, being: 4 teachers and 9 assistants, all men, and 4 school managers, one man and three women. For the data analysis, first the contents of the questionnaire were presented and discussed, and then the interviews' data were organized in four categories: 1) Formative and professional trajectories of the researched subjects; 2) Sexual division of work; 3) Conflicts and dilemmas faced by male professionals in early childhood education; and 4) Importance of the presence and male reference in Early Childhood Education. The results point to the sexual division of labor marked by the historically constituted sexist view, perceived implicitly and explicitly in the performance of the subjects investigated, in addition to reflecting on the looks of suspicion, prejudice, fear, discrimination, among other aspects perceived in the speeches of these male professionals who work in early childhood education in Goiânia. In addition, it was evident that the presence of men in early childhood education breaks with the sexual division of labor, which is the thesis defended by this study. We noticed the sensitivity of this theme and the difficulty of some respondents in unveiling some facts experienced in the institutions. Furthermore, it was evident the lack of legislation regulating the activities of the educational activities assistants and the need to train these professionals to work with young children. Furthermore, the importance of male professionals in early childhood education is highlighted, as well as the deconstruction of representations marked by gender relations. Thus, the results obtained point to the need for new studies and debates on this issue in order to break with the historical sexist inequality that permeates this sensitive theme.